Gypsum utilization on selective reduction of limonitic laterite nickel - Sungging Pintowantoro; Rafiedhia Abel Muhammad Pasha; Fakhreza Abdul (Results in Engineering, 2021)
The world's nickel demand is increasing, especially with more countries starting to produce battery-based electric vehicles. Currently, nickel is the main element used for the fabrication of Nickel Manganese Cobalt (NMC) batteries. Nickel itself can be extracted from its ore through pyrometallurgical route. Selective reduction of nickel using a selective reducing agent is needed in order to produce nickel with appropriate grade. This study aims to study the possibility of gypsum as a selective reducing agent in the direct reduction process. In this process, laterite nickel ores with nickel content of 1.59% were crushed and classified until the feed particle size was smaller than 50 standard mesh. The crushed laterite nickel ores were then mixed with gypsum and a binder material to undergo briquetting and drying. A bed mix composed of limestone powder and coal was added into the crucible alongside the ore briquettes. Carbothermic reduction was done at 1400 °C for 6 h. The product was then crushed and separated through magnetic separation. The reduced product's chemical composition was analyzed using Scanning Electron Microscope-Energy Dispersive X-Ray and X-Ray Diffractometer. The results indicate that gypsum can provide a selective effect on the direct reduction process of laterite nickel ore. A selective effect that lowers the grade of iron can occur due to the formation of iron sulfides. The use of 12% gypsum was able to produce a product with Ni grade of 4.13%, Ni recovery of 91.81%, and selectivity factor of 5.72. Therefore, based on the results of this experiment, gypsum minerals can be used as a potential low-cost alternative as an additive for nickel selective reduction.